Protection of Hajj and Umrah Pilgrims from Fraud: Evidence from Indonesia - Setiawan, Nanang; Soewarno, Noorlailie (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
This study explores the prevalence of fraud targeting Hajj and Umrah pilgrims in Indonesia and examines the government's role in protecting these pilgrims. Utilizing a qualitative approach, data were collected through observations and interviews with key stakeholders, including officials from the Ministry of Religious Affairs (MoRA), travel agency representatives, and Umrah pilgrims in an East Java district. The findings reveal that excessive trust in Hajj and Umrah travel agencies without verifying their licenses and track records is the primary cause of fraud. Additionally, Ponzi schemes by certain travel agencies, offering low-cost Umrah packages with uncertain travel schedules, further exacerbate the issue. The government's "Lima Pasti Umrah" (Five Guaranteed Umrahs) program is highlighted as a crucial preventive measure against fraud. This study enhances understanding of the protective measures available for Hajj and Umrah pilgrims in Indonesia and provides recommendations for improving fraud prevention programs for future pilgrims.======================================================================================================== ABSTRAK – Perlindungan Jemaah Haji dan Umrah dari Penipuan: Praktik di Indonesia. Penelitian ini mengkaji prevalensi penipuan yang menyasar jemaah haji dan umrah di Indonesia serta menganalisis peran pemerintah dalam melindungi para jemaah tersebut. Penelitian ini menggunakan pendekatan kualitatif, di mana data dikumpulkan melalui observasi dan wawancara dengan para pemangku kepentingan utama, termasuk pejabat Kementerian Agama (Kemenag), perwakilan biro travel, dan jemaah umrah di salah satu kabupaten di Jawa Timur. Temuan penelitian menunjukkan bahwa kepercayaan berlebihan terhadap biro travel haji dan umrah tanpa memeriksa izin dan rekam jejak mereka menjadi faktor utama terjadinya penipuan. Selain itu, praktik skema Ponzi yang dilakukan oleh oknum biro travel, yang menawarkan paket umrah murah dengan jadwal perjalanan yang tidak pasti, semakin memperparah masalah ini. Sebagai langkah antisipatif, pemerintah membuat Program "Lima Pasti Umrah”. Hasil kajian diharapkan dapat meningkatkan literasi mengenai perlindungan bagi jemaah haji dan umrah di Indonesia dan memberikan rekomendasi program pencegahan penipuan bagi jemaah di masa mendatang.